2021
DOI: 10.31083/j.rcm2203091
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative meta-synthesis of patients with heart failure perceived needs

Abstract: Supportive care may have significant input into the treatment of patients with heart failure (HF). Support, understanding and being treated as a whole and unique person are vital for patients with HF. In order to develop a person-centred program, it is important to know patients' needs from their perspectives. The aim of the current review and meta-synthesis was to explore the needs of patients with HF from their perspective. A qualitative review was conducted using the keywords: (''needs" OR "need") AND (''he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 47 publications
(103 reference statements)
4
10
3
Order By: Relevance
“…The remaining participants suggested that the treatment should consider aspects of patients' personal life, such as quality of life, and should be modified, especially with regard to medical therapies. These results are in line with the literature, which also suggests that individual tailoring of treatment is beneficial regarding treatment burden management, ameliorates care adaptation to everyday life and engages patients in improving their health ( 20 22 ). In addition, some HF patients not only expressed the need for a change of medical treatment, likely associated with polypharmacy and treatment burden ( 38 , 39 ), but also the need of improving their quality of life.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The remaining participants suggested that the treatment should consider aspects of patients' personal life, such as quality of life, and should be modified, especially with regard to medical therapies. These results are in line with the literature, which also suggests that individual tailoring of treatment is beneficial regarding treatment burden management, ameliorates care adaptation to everyday life and engages patients in improving their health ( 20 22 ). In addition, some HF patients not only expressed the need for a change of medical treatment, likely associated with polypharmacy and treatment burden ( 38 , 39 ), but also the need of improving their quality of life.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning monitoring, more than three quarters of the participants wished that the CM would check symptoms (such as shortness of breath, weight gain, blood pressure, glucose, and cholesterol) as specified in the cards, whereas the rest of the participants preferred assistance with medication prescription, following treatment recommendations and additional medical information. The results are supported by previous studies ( 20 , 21 ) and highlight the importance of addressing and monitoring needs among elderly HF patients for clinical stability ( 34 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations